MODEL PEMBELAJARAN KONTEKSTUAL IPA MELALUI PENDEKATAN OUTDOOR LEARNING DI SDN SUMURJALAK 2 PLUMPANG TUBAN - Midya Yuli Amreta; Ahmad Farid Utsman (PREMIERE : Journal of Islamic Elementary Education, 2020)
Learning contextual on IPA is learning of nature science who insists on the links between matter learning of surely clear. This study attempts to described and analyze learning model contextual IPA in SDN sumurjalak 2 plumpang, described and analyze outdoor learning in SDN sumurjalak 2 plumpang , and described and analyze learning model contextual IPA through outdoor learning in SDN sumurjalak 2 plumpang .This study adopted qualitative approaches that uses the design cases. The data collection was done through technique interview, observation, and documentation. Technique data analysis covering reduction data, presentation of data, and the withdrawal of conclusion. Informants in this research among others Headmaster, teachers, and school tuition. The results of research has done shown that: ( 1 ) learning science using contextual learning model it can enhance understanding drafts participants students.In learning use contextual teachers capable of mengondisikan students by stressing towards the process of full involvement students to own mengkostruksikan matter learned and connecting with the real life causing students to can use them in their lives.( 2 ) outdoor approach learning is an alternative to science suitable learning adventure and observation directly in the real environment around with link science, environment, and the technology.( 3 ) contextual learning model in learning science capable of learning constructive provides science and give meaningful study results for learners.Students can find arrange their own that they can be meaningful and unforgetable. Students get easier to understand the content of learning, they also have higher critical thinking and creative on question and answer session in learning science.